A TaSnRK1α-TaCAT2 model mediates resistance to Fusarium crown rot by scavenging ROS in common wheat - Xia Yang; Leilei Zhang; Jiajie Wei; Lexin Liu; Di Liu; Xiangning Yan; Minjie Yuan; Lingran Zhang; Ning Zhang; Yan Ren; Feng Chen (Nature Communications)
Abstract Fusarium crown rot (FCR) is a serious underlying disease to threaten wheat yield and quality recently. Here, we identify a catalase antioxidant enzyme (TaCAT2) through genome wide association study (GWAS) and whole-exome sequencing (WES) in two nested bi-parental populations. We verify the function of TaCAT2 regulating wheat FCR resistance by genetic transformation. Moreover, we screen a sucrose non-fermenting-1-related protein kinase alpha subunit (TaSnRK1α) interacting with TaCAT2, and subsequently find that TaSnRK1α phosphorylates TaCAT2. We next identify an FCR-resistance haplotype TaCAT2Ser214, and confirm that Ser214 of TaCAT2 is a key phosphorylation site for TaSnRK1α. We also find that TaSnRK1α results in higher protein accumulation in TaCAT2Ser214 than in TaCAT2Thr214, which possibly contribute to scavenging ROS (reactive oxygen species) in TaCAT2Ser214 wheat plants. Furthermore, the function of TaSnRK1α regulating FCR resistance is verified by genetic transformation. Taken together, we propose a TaSnRK1α-TaCAT2 model to mediate FCR resistance by scavenging the ROS in wheat plants.